Implementation of species protection act for the conservation of Tanimbar corella, Cacatua goffiniana (Roselaar & Michels, 2004) - Tri Haryoko (MBI & UNS Solo, 2021)
Abstract. Haryoko T, O’Hara M, Mioduszewska B, Sutrisno H, Prasetyo LB, Mardiastuti A. 2021. Implementation of species protection act for the conservation of Tanimbar corella, Cacatua goffiniana (Roselaar & Michels, 2004). Biodiversitas 22: 1733-1740. Birds are among the most favored pet animals and are nurtured because of their melodious voice, intelligence, and beautiful feathers. Therefore, these animals are usually traded in both local and international markets. Wild bird trades are dominated by species from the order Passeriformes/songbirds and Psittaciformes/parrots. Furthermore, one of the Psittaciformes groups that are in high demand as a pet is the cockatoos. The Goffin’s cockatoo or Tanimbar corella/Cacatua goffiniana (Roselaar & Michels,2004)is one of seven species of parrots native to Indonesia and has been traded for decades. This endemic bird from the Tanimbar Islands (Maluku Province) has been protected by the Indonesian government since 1990 and has been on the CITES Appendix I since 1992. Therefore, this study aims to review the harvesting of C. goffiniana and the effect the bird's protection status has on its trade. It was conducted by investigating the legal trade data for 1981-2018, information on illegal trade, and ex-situ conservation of this species. The review on the trade of C. goffiniana was assessed using descriptive analysis. Furthermore, Independent Samples T-Test was used to determine the differences between the number of C. goffiniana traded before and after the bird was listed in Appendix I CITES and protected by Indonesia's law. The results showed that the number of exported Cacatua goffiniana for 38 years to 34 countries was 151,684. Furthermore, the United States of America was the largest importer with a total of 118,356/78.03%. It was discovered that the number of birds legally exported by Indonesia has decreased dramatically since 1990 because these animals are protected by Indonesian law. Consequently, there was a significant difference between the number traded before and after their designation as protected species. The nonparametric correlation between protection status and Appendix I CITES listing to the number of these animals traded was statistically significant. Finally, existing conservation practices involve efforts to restock the population by means of captive breeding programs. However, as conservation agencies have shown little success in breeding these species, the efforts are not sufficient to fulfill the demand. Therefore, illegal trade is still a major threat to the natural populations.